Study of Natural Radioactivity Levels and Radon/Thoron Release Potential of Bedrock and Soil in Southeastern Ireland - Crowley, Quentin (My University, 2021)
Radon (222Rn) and thoron (220Rn) account for almost two-thirds of the annual average radiation dose received by the Irish population. A detailed study of natural radioactivity levels and radon and thoron exhalation rates was carried out in a legislatively designated “high radon” area, as based on existing indoor radon measurements. Indoor radon concentrations, airborne radiometric data and stream sediment geochemistry were collated, and a set of soil samples were taken from the study area. The exhalation rates of radon (E222Rn) and thoron (E220Rn) for collected samples were determined in the laboratory. The resultant data were classified based on geological and soil type parameters. Geological boundaries were found to be robust classifiers for radon exhalation rates and radon-related variables, whilst soil type classification better differentiates thoron exhalation rates and correlated variables. Linear models were developed to predict the radon and thoron exhalation rates of the study area. Distribution maps of radon and thoron exhalation rates (range: E222Rn [0.15–1.84] and E220Rn [475–3029] Bq m−2 h−1) and annual effective dose (with a mean value of 0.84 mSv y−1) are presented. For some parts of the study area, the calculated annual effective dose exceeds the recommended level of 1 mSv y−1, illustrating a significant radiation risk. Airborne radiometric data were found to be a powerful and fast tool for the prediction of geogenic radon and thoron risk. This robust method can be used for other areas where airborne radiometric data are available.
PUBLISHED
Keywords: Radon and thoron exhalation rates; Airborne radiometric; Radiation risk; Geological combination and soil type; Smart & Sustainable Planet; INDOOR RADON; LUNG CANCER; Radon Priority Area; THORON